Information Computing and Applications 4th International Conference, ICICA 2013, Singapore, August 16-18, 2013, Revised Selected Papers, Part I - Yang, Yuhang; Ma, Maode; Liu, Baoxiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This two-volume set of CCIS 391 and CCIS 392 constitutes the refereed proceedings of the Fourth International Conference on Information Computing and Applications, ICICA 2013, held in Singapore, in August 2013. The 126 revised full papers presented in both volumes were carefully reviewed and selected from 665 submissions. The papers are organized in topical sections on Internet computing and applications; engineering management and applications; intelligent computing and applications; control engineering and applications; cloud and evolutionary computing; knowledge management and applications; computational statistics and applications.
Internet computing and applications -- Engineering management and applications -- Intelligent computing and applications -- Control engineering and applications -- Cloud and evolutionary computing -- Knowledge management and applications -- Computational statistics and applications.
Keywords: Computer science; Computer Communication Networks; Multimedia systems; Electronic data processing; Computer simulation; Information Systems; Computer Science; Computer Communication Networks; Management of Computing and Information Systems; Simulation and Modeling; Computing Methodologies; Information Systems Applications (incl. Internet).; Multimedia Information Systems